Combination of Bacillus velezensis RC218 and chitosan to control Fusarium head blight on bread and durum wheat under greenhouse and field conditions - Palazzini, Juan Manuel (2022)
Fusarium graminearum sensu stricto is, worldwide, the main causal agent of Fusarium head blight in small cereal crops such as wheat, barley, and oat. The pathogen causes not only reductions in yield and grain quality but also contamination with type-B trichothecenes such as deoxynivalenol. Prevention strategies include the use of less susceptible cultivars through breeding programs, cultural practices, crop rotation, fungicide application, or a combination of them through an integrated pest management. Additionally, the use of more eco-friendly strategies by the evaluation of microorganisms and natural products is increasing. The effect of combining Bacillus velezensis RC218 and chitosan on Fusarium Head Blight (FHB) and deoxynivalenol accumulation under greenhouse and field conditions in bread and durum wheat was evaluated. Under greenhouse conditions, both B. velezensis RC218 and chitosan (0.1%) demonstrated FHB control, diminishing the severity by 38 and 27%, respectively, while the combined treatment resulted in an increased reduction of 54% on bread wheat. Field trials on bread wheat showed a biocontrol reduction in FHB by 18 to 53%, and chitosan was effective only during the first year (48% reduction); surprisingly, the combination of these active principles allowed the control of FHB disease severity by 39 and 36.7% during the two harvest seasons evaluated (2017/18, 2018/19). On durum wheat, the combined treatment showed a 54.3% disease severity reduction. A reduction in DON accumulation in harvested grains was observed for either bacteria, chitosan, or their combination, with reductions of 50.3, 68, and 64.5%, respectively, versus the control.